Adsorptive Removal of Cadmium from Aqueous Solution onto Na-Bentonite - Liu, Zhi-rong; Zhou, Shao-qi (Asian Journal of Chemistry, 2010)
The removal of cadmium from aqueous solution on the Na-bentonite has been studied under static conditions. Experiments were carried out as a function of solution pH, dosage of Na-bentonite, contact time. The adsorption equilibrium for cadmium onto Na-bentonite is reached in 120 min. The adsorption of cadmium is pH dependent in the pH range 2-8. The kinetic process of adsorption can be described by the pseudo-second-order kinetic equation satisfactorily.